Structure of photosystem I-LHCI-LHCII from the green alga Chlamydomonas reinhardtii in State 2 - Huang, Zihui; Shen, Liangliang; Wang, Wenda; Mao, Zhiyuan; Yi, Xiaohan; Kuang, Tingyun; Shen, Jian-Ren; Zhang, Xing; Han, Guangye (Nature communications, 2021)
Photosystem I (PSI) and II (PSII) balance their light energy distribution absorbed by their light-harvesting complexes (LHCs) through state transition to maintain the maximum photosynthetic performance and to avoid photodamage. In state 2, a part of LHCII moves to PSI, forming a PSI-LHCI-LHCII supercomplex. The green alga Chlamydomonas reinhardtii exhibits state transition to a far larger extent than higher plants. Here we report the cryo-electron microscopy structure of a PSI-LHCI-LHCII supercomplex in state 2 from C. reinhardtii at 3.42 Å resolution. The result reveals that the PSI-LHCI-LHCII of C. reinhardtii binds two LHCII trimers in addition to ten LHCI subunits. The PSI core subunits PsaO and PsaH, which were missed or not well-resolved in previous Cr-PSI-LHCI structures, are observed. The present results reveal the organization and assembly of PSI core subunits, LHCI and LHCII, pigment arrangement, and possible pathways of energy transfer from peripheral antennae to the PSI core. Photosystems (PS) I and II undergo state transitions to optimize photosynthesis and photoprotection. Here the authors report a cryo-electron microscopy structure of the state 2 PSI-LHCI-LHCII supercomplex from C. reinhardtii revealing subunit organization and possible pathways of energy transfer.